1986
DOI: 10.1111/j.1432-1033.1986.tb09683.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of fatty acid activation of the uncoupling protein in brown adipocytes and mitochondria from the guinea-pig

Abstract: Brown adipocytes from cold‐adapted guinea‐pigs (C‐cells) are more sensitive to uncoupling by exogenous palmitate than are cells from warm‐adapted animals (W‐cells) with much less uncoupling protein. Half‐maximal respiratory stimulation of C‐cells requires 80 nM free palmitate. Noradrenaline‐stimulated lipolysis is not rate‐limiting for the respiration of either C‐cells or W‐cells. Half‐maximal stimulation of fatty acid oxidation by mitochondria from warm‐adapted guinea‐pigs (W‐mitochondria) and cold‐adapted gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 31 publications
2
41
1
Order By: Relevance
“…Another pathway known to transport CI-in mitochondria is the uncoupling protein of brown-adipose-tissue mitochondria; however, in contrast with the inner membrane anion channel this pathway is regulated by fatty acids [20,21], GDP [22] (however, see [14]) and is not regulated by matrix protons or Mg". Recently, however, it has been shown that the activity of the uncoupling protein is modified by thiolreactive reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Another pathway known to transport CI-in mitochondria is the uncoupling protein of brown-adipose-tissue mitochondria; however, in contrast with the inner membrane anion channel this pathway is regulated by fatty acids [20,21], GDP [22] (however, see [14]) and is not regulated by matrix protons or Mg". Recently, however, it has been shown that the activity of the uncoupling protein is modified by thiolreactive reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from other types of mitochondria they possess the uncoupling protein (UP), a unique proton translocator [2,3], converting A/~H + into heat. H + fluxes through the UP are inhibited by purine nucleotides [4][5][6][7][8] and activated by fatty acids [3,[8][9][10]. Both regulatory mechanisms were also demonstrated in a reconstituted system [3], but the activation by fatty acids was disputed in another laboratory [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, FA may play a role as endogenous natural protonophores in biological membranes [17] which is extremely important in considering dissipative H ÷ currents in mitochondria lacking UP. The stronger uncoupling effect of FA in BAT mitochondria clearly reflects activation of H ÷ transport through UP and correlates with the exclusive occurrence of UP in BAT [9,10]. In our work we used a controlled removal of endogenous fatty acid from BAT mitochondria by a carnitine cycle [8,9,[18][19][20] in order to estimate the interrelationship between effects of purine nucleotides and fatty acids on UP function.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating fatty acids are bound to albumin, with typical molar ratios in the range 1-2 for the human (442) and up to 3 for the fasted rat (496). The free, unbound, fatty acid concentration under these conditions is only ϳ10 -20 nM (105,442). While the need for albumin binding is generally appreciated in the literature, molar ratios of 6:1 or even higher have been employed in vitro (144,285,332,472), producing unbound fatty acid concentrations close to 1 M, or 100 times higher than the normal physiological range (FIGURE 8A).…”
Section: E Fatty Acidsmentioning
confidence: 99%